Selective Termination for Fetal Anomaly in Twin Pregnancy - Putri Mirani (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective: To discussed the ethical aspects, the technique, optimal timing and the possible outcome of selective termination in anomalous twin pregnancy. Case description: A 28-year old primigravida, 21 weeks twin gestation, with giant hygroma coli in one fetus. The normal fetus was compressed by the anomalous fetus with oligohydramnios. The parent decided to undergo selective termination of the abnormal fetus. The procedure perform was intracardiac injection of potassium chloride (KCl). Eight milliliters of KCl were injected into fetal cardiac, followed by bradicardia and asystole of the anomalous twin. A week after the procedure, the normal fetus also died and delivered spontaneously after induction. Conclusion: Selective termination for fetal anomaly in twin pregnancy have some aspects to be considered. Keywords: selective feticide, selective termination